4(2+b)+(-2b)+-1-(2+b)-b=5

Simple and best practice solution for 4(2+b)+(-2b)+-1-(2+b)-b=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2+b)+(-2b)+-1-(2+b)-b=5 equation:


Simplifying
4(2 + b) + (-2b) + -1 + -1(2 + b) + -1b = 5
(2 * 4 + b * 4) + (-2b) + -1 + -1(2 + b) + -1b = 5
(8 + 4b) + (-2b) + -1 + -1(2 + b) + -1b = 5
8 + 4b + (-2b) + -1 + (2 * -1 + b * -1) + -1b = 5
8 + 4b + (-2b) + -1 + (-2 + -1b) + -1b = 5

Reorder the terms:
8 + -1 + -2 + 4b + (-2b) + -1b + -1b = 5

Combine like terms: 8 + -1 = 7
7 + -2 + 4b + (-2b) + -1b + -1b = 5

Combine like terms: 7 + -2 = 5
5 + 4b + (-2b) + -1b + -1b = 5

Combine like terms: 4b + (-2b) = 2b
5 + 2b + -1b + -1b = 5

Combine like terms: 2b + -1b = 1b
5 + 1b + -1b = 5

Combine like terms: 1b + -1b = 0
5 + 0 = 5
5 = 5

Add '-5' to each side of the equation.
5 + -5 = 5 + -5

Combine like terms: 5 + -5 = 0
0 = 5 + -5

Combine like terms: 5 + -5 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -30.3+0.1p=0.9p+5.3 | | 2cos(4x)=-1.5 | | 5+7x=26 | | n/5+1=2+3 | | 14=x+3 | | x-8.5=-5.5 | | x-39=13 | | 2x+4x-16-12b=24x+8-3x+6b | | 120+80= | | 10+x=48 | | 7x-6=23 | | 2-3x=6-5x | | x-7.6=-3.9 | | 6x-20+4x=180 | | 7(3x+5)=2(4x+13) | | w/3-4=1 | | 4(2+b)+(-2b)+-1-a-b=5 | | -7625+185x=12790 | | (2x-5)-(x+1)=10 | | 2x+5=7x-10 | | 7+5x=-3x+31 | | m/2-2=4 | | 56-x=5 | | 7x-6=3x+10 | | 6x-10=8-3x | | x/2+3=7 | | b-37=8 | | -4x-15=2x+21 | | y=-0.125x^2+1.375x+1.5 | | 3b+4.4=2.6+-6b | | -16y-8(3y-2)=-24 | | 11.7+-2x=x |

Equations solver categories